Religion and Art - XI , Wang (Journal of Research for Christianity in China (JRCC), 2025)
Author: Richard Wagner (1813–1883), German musician.Translator: XIi Wang, Assistant Professor at the College of Liberal Arts, Fujian Fuyao University of Science and Technology; PhD in Philosophy from Peking University.Proofreader: GUO Chun, Doctoral Candidate (Class of 2023), Department of Musicology, Central Conservatory of Music.This translation is adapted from Richard Wagner: Über Staat und Religion / Religion und Kunst, Berlin: Herausgegeben von Karl-Maria Guth, 2017. Unless specifically marked as original notes, all unmarked annotations in this text are translator's notes.